Prevalence and characteristics of HTLV-associated uveitis in patients from Bahia, an endemic area for HTLV − 1 in Brazil - Daniele Piai Ozores; Regina Rathsam Pinheiro; Ney Boa-Sorte; Maurício Campos e Silva Dias; Raianne Silva Lima; Thessika Hialla Almeida Araújo; Bernardo Galvão-Castro; Maria Fernanda Rios Grassi (Virology Journal, 2023)
Abstract Background HTLV-1-associated uveitis (HAU) is an inflammatory reaction of the choroid, retina, optic nerve and vitreous that can lead to vision impairment. The worldwide prevalence of HAU varies widely. Objective To determine the prevalence of HAU in patients from Salvador, Bahia-Brazil, and describe uveitis type and associated symptoms. Methods Cross-sectional analytical study to determine the prevalence of uveitis in HTLV-1-infected patients recruited in Bahia, Brazil, a region considered endemic for HTLV-1. Patients were enrolled at a local reference center for HTLV (infected) and at an outpatient ophthalmology clinic (noninfected group). All patients were examined by the same ophthalmologist following a single protocol. Prevalence ratios (PR) were calculated. Results A total of 168 consecutively examined HTLV-1-infected patients and 410 noninfected patients (randomly selected) were included. Females predominated (82.1%) in the HTLV-1-infected group (versus 64.4% in the uninfected group) (p < 0.001). The mean age of infected and uninfected patients was 53.2 and 62.8 years, respectively (p < 0.001). The prevalence of uveitis in HTLV-1+ and HTLV-1− patients was 7.14% and 0.73%, respectively (PR = 9.76; 95CI%:2.79–34.15; p < 0.01). Bilateral intermediate uveitis, associated with symptoms including visual disturbances and floaters, was most commonly identified in the HTLV-1-infected patients, whereas unilateral anterior uveitis, in association with symptoms such as blurring and ocular pain, was more common in the uninfected group. Conclusion The prevalence of uveitis in patients with HTLV-1 was markedly higher than in uninfected subjects. HAU patients were mostly asymptomatic and exhibited bilateral presentation, with uveitis more frequently localized in the intermediate chamber.